LAJU PERTUMBUHAN IKAN KOAN (Ctenopharyngodon idela c.v) DENGAN BERBAGAI TINGKAT PEMBERIAN PAKAN - FORITA DYAH ARIANTI (JURNAL LITBANG PROVINSI JAWA TENGAH, 2005)
The research aimed to know the effect of feeding amount daily of Koan Fish (Ctenopharyngodon idela c.v) sized on 5-8 cm length, 2.5 g weight and strew population on fish per I 000 cc of water. Floury feeding contents 40.92 % of protein have been given twice a day on 09.00 a.m and 17.00 p.m, with the same amount. Dosage adjustment have been done once a week after weighing the fish. Box culture used consist of twelve box (30 x 30 x 30 Cm) and strew in 20 fish per box. The experiment used is Randomized Complete Design with four(4) levels of feeding( 3. 6. 9 and 12 % offish weight) as treatment in three replications. The data is then analyzed using Analysis of Variance (ANOVA) and Least Significant Difference (LSD) for meant compirisons. No dead fish incidence in the experiment. The growth acceleration of fish per day increased from 0.19 % to 1.23 % as the feeding level increased from 3 % - 12 % of fish weight per day. The maximum growth acceleration of fish per day was 1.23 % on 10.83 % offish weight per day feeding level with 10.20 % of feeding efficiency. The optimum growth acceleration of 0.80 % ·have been found on 5.74. % feeding level of fish weight per day, with 15.93 % of feeding efficiency